Dislocation density dependence of stimulated emission characteristics in AlGaN/Al multiquantum wells. Issue 11 (24th October 2013) - Matsubara, Yuko; Yamada, Tomoaki; Takeda, Kenichiro; Iwaya, Motoaki; Takeuchi, Tetsuya; Kamiyama, Satoshi; Akasaki, Isamu; Amano, Hiroshi; Yamaguchi, Hiroshi; Kumakura, Kazuhide
Abstract We investigated dislocation density dependence on stimulated emission characteristics of AlGaN/AlN multiquantum wells (MQWs: emission wavelength of approximately 285 nm) on AlN templates with various dislocation densities. We found that the stimulated emission characteristics of the deep UV MQWs were strongly dependent on the dislocation densities. A reduction of the dislocation densities is very important in order to realize good stimulated emission characteristics of deep UV MQWs. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)